The Impact Of Latent Defects On The Public Buildings In Malaysia - Talib, Roslan (2022)
Building defects become more complex issues than what we are thinking and affected severely to the valuable assets found within the interior spaces when real defects; the leakage defects occurred. Literature research revealed that compared to fire or structural defects; building defects provides more problematic scenarios upon plummeting with seen or latent defects. Eviler anticipated when latent defects arise during pre, during or post-construction stage. Thus, the purpose of the study is steering to aim at having nil construction defects. With zero or fewer building defects affected the exterior or the interior of the building, the quality of the buildings will be at the highest and impetus the building’s commercial value. Next, the objective of the research is to control building defects from keep on happening and keep on repeating them. It’s about time, something needs to be done to prevent it, seriously. Initiated with the PILOT test, accumulating comprehensive real project data, FGD cyber sessions, face to face interviews as well as systematic online survey; the research can accumulate enough amount of quality data eligible to support strong study conclusion. Finally, the findings measured out that building defects; regardless it’s latent or none; still play a foremost part in giving nuisance to the building construction players. With the mammon collection of defects data, the comprehensive and detailed statistical analysis can be done systematically; thus, proving the suggested outlined hypotheses and filling out the research gaps.